ANALISIS STRATEGI KOMUNIKASI BISNIS KELUARGA TAHU BUNGKENG DALAM MENINGKATKAN LOYALITAS PELANGGAN: (Studi Kasus pada Bisnis Keluarga Produk Makanan Tahu Bungkeng di Kabupaten Sumedang) - Syaefulloh, Iqbal (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Tahu Sumedang is a food product that is not only known in Sumedang Regency, but is known throughout the country. Tahu Bungkeng is a pioneer of Tahu Sumedang which has been established since 1917. Tahu Bungkeng is a food company managed by the Ong family. The method used by researchers is qualitative, allowing researchers to explore the research subject in depth and understand the wider context. and data collection techniques by conducting interviews and direct observation. This research will explain in detail why the Bungkeng Family Business was able to survive for four generations and still exists today. The family business communication strategy is carried out primarily in determining who will be the successor to continue the family business relay. This research concludes that the Tahu Bungkeng business communication strategy that is still being implemented today is still very effective in being implemented in the family business journey. AIDA theory is a theoretical approach used by researchers to measure the extent to which this family business communication strategy is able to survive and develop its business. Customer loyalty is also very important in a business context because it has a significant positive impact. It turns out that loyal consumers have been buying Tahu Bungkeng products for a very long time, some have even reached the next generation, meaning that Tahu Bungkeng is able to maintain consistent product and service quality so that it is still very popular with consumers.